2017
DOI: 10.1038/nutd.2016.35
|View full text |Cite
|
Sign up to set email alerts
|

An interactive web-based intervention on nutritional status, physical activity and health-related quality of life in patient with metabolic syndrome: a randomized-controlled trial (The Red Ruby Study)

Abstract: Background/Objectives:Physical inactivity and unhealthy nutritional behaviors are recognized as the key factors in the cause and management of metabolic syndrome (MetS). The effectiveness of interactive web-based interventions on dietary intakes, physical activity and health-related quality of life (HRQOL) among people with MetS is currently unknown.Methods:The two-arm randomized-controlled trial was conducted for patients with MetS from June through December 2012 in Tehran, Iran. Participants (n=160) were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
67
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 47 publications
(37 reference statements)
3
67
1
2
Order By: Relevance
“…Moreover, adults with multiple chronic illnesses appeared to receive similar benefit from recommended levels of PA. These results are consistent with randomized controlled trials that have shown increases in PA with simultaneous increases in HRQOL [19,20,21,22]. These findings are further supported by studies that have shown increased HRQOL in physically active participants with chronic diseases [23][24][25][26][27][28][29].…”
Section: Odds Ratios (Ors)supporting
confidence: 80%
“…Moreover, adults with multiple chronic illnesses appeared to receive similar benefit from recommended levels of PA. These results are consistent with randomized controlled trials that have shown increases in PA with simultaneous increases in HRQOL [19,20,21,22]. These findings are further supported by studies that have shown increased HRQOL in physically active participants with chronic diseases [23][24][25][26][27][28][29].…”
Section: Odds Ratios (Ors)supporting
confidence: 80%
“…The results obtained are important for the assessment of the multiple facets of the pathogenicity of the metabolic syndrome (74)(75), in which environmental factors play an overwhelming role.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a previous study supported diabetics’ behavioural changes using telephone follow‐ups and was also unable to improve exercise habits (Sakane et al, ). Studies that have been successful in bringing about continuous behavioural change with respect to exercise have involved group‐based exercise (Santanasto et al, ), a way to manage exercise records (Aguiar et al, ) and an interactive web‐based programme tailored to each individual (Jahangiry, Montazeri, Najafi, Yaseri, & Farhangi, ). Modifying our programme to include more intensive and interactive content and modifying the environment where our participants exercise may be necessary to improve our outcomes.…”
Section: Discussionmentioning
confidence: 99%